From Outages to Excellence: Building Resilience with Disaster Recovery in the Cloud - Karthik Venkatesh Ratnam, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Cloud-based disaster recovery (DR) has emerged as a transformative approach to building organizational resilience, fundamentally changing how businesses protect their critical systems and data. This article explores the evolution from traditional DR methods to modern cloud-based solutions, examining their architectural components, implementation strategies across various industries, and integration with advanced technologies. Through analysis of real-world applications and case studies, it demonstrates how cloud DR solutions enable organizations to achieve superior recovery objectives while maintaining cost-effectiveness and scalability. This article highlights the significance of automated monitoring, AI-driven anomaly detection, and continuous testing in establishing robust DR strategies. Furthermore, it focuses on industry-specific challenges and solutions, providing insights into best practices for optimizing cloud DR implementations. It also indicates that organizations embracing cloud-based DR not only enhance their business continuity capabilities but also gain strategic advantages in adaptability and operational excellence. This comprehensive article on cloud DR encompasses current practices, emerging trends, and future challenges, offering valuable insights for technology leaders and practitioners in the field of disaster recovery and business continuity.
Keywords: Cloud Disaster Recovery; Business Continuity; Automated Failover; Multi-region Resilience; Recovery Automation